New Roles for Educators in Disruption World - Singharaj, Arpaporn; Fakkao, Sawai (Thammasat Journal, 2022)
Nowadays, new technologies have played an important role in changing the world which may be called “disruptive technologies”. They affect the lives of all people, making the world in a state of volatility, uncertainty, complexity, and ambiguity. The objective of this article is to present perspective on the new role of educators to the changing world in three key areas: 1) Self-improvement to be aware of the changing world, 2) Development of the ability to manage learning and 3) Assessing learning outcomes of learners. The goal is to transform the concept of traditional learning management into a learning management that aims to improve the learners’ ability to live in a dynamic world. The recommendations for Thai educators are as follows: 1) Developing themselves to be knowledgeable in various fields, knowledge and essential skills in the future for learners, 2) Transition instruction from teacher-centered and content based learning to learning management focused on developing learner competencies and 3) Applying holistic measurements and assessments that encompass knowledge, Skills/competencies and desirable characteristics of the learners by using authentic measurement and assessment.